Correlation between obesity and successful ovulation induction with Clomiphene citrate - Rida Eka Setiani; Sri Ratna Dwiningsih; Gadis Meinar Sari (Universitas Muhammadiyah Surabaya, 2022)
ABSTRACTOvulation induction with clomiphene citrate is a hormonal therapy for infertile women with impaired ovarian function caused by dysregulation of the hypothalamus and pituitary, affecting egg development and ovulation. Several factors, such as obesity, influence the success rate of treatment with clomiphene citrate. According to the Asia-Pacific classification, obesity was classified into two categories, obesity type I (25-29,9 kg/m2) and obesity type II (≥30 kg/m2). The success rate of ovulation induction with clomiphene citrate in obese infertile women at Graha Amerta Fertility Clinic in Dr. Soetomo General Hospital on July 2019 – July 2020 was about 22.8%. The research aimed to analyze the correlation between obesity with successful ovulation induction with clomiphene citrate. This research method was observational analytic research with a cross-sectional approach. The data were collected from medical records of infertile obese women who undergo ovulation induction with clomiphene citrate. According to inclusion criteria, the number of samples is 79 cycles of infertile obese women who undergo ovulation induction with clomiphene citrate. Data analysis using Chi-square test. The result showed that successful ovulation induction in obese type I was 17.7% and in obese type II was 5.1%. There was a correlation between obesity with successful ovulation induction with clomiphene citrate (p=0.009). In conclusion, there was a correlation between obesity with successful ovulation induction.Keyword : ovulation induction, clomiphene citrate, obeseCorrespondence : sri-r-d@fk.unair.ac.idation induction.